Immune response at 12–23 months following a single dose of Vero cell culture-derived Japanese encephalitis (JE) vaccine in adults previously vaccinated with mouse brain-derived JE vaccine. Issue 44 (14th October 2020) - Krow-Lucal, Elisabeth R.; Laven, Janeen; Perry, Lori; Biggerstaff, Brad J.; Johnson, Barbara W.; Hollis, Ewell; Fischer, Marc; Woolpert, Tabitha; Hills, Susan L.
Abstract: Background: Japanese encephalitis (JE) virus is an important cause of neurological disease in Asia. JE vaccine is recommended for travelers with higher JE risk itineraries. Inactivated Vero cell culture-derived JE vaccine (JE-VC) is the only JE vaccine currently available in the United States. An inactivated mouse brain-derived JE vaccine (JE-MB) previously was available but production was discontinued. One JE-VC dose administered to adults previously vaccinated with ≥3 doses of JE-MB provides good short-term protection for at least one month, but data on longer-term protection are limited. We evaluated non-inferiority of the JE virus neutralizing antibody response at 12–23 months in JE-MB-vaccinated adults administered one JE-VC dose compared with JE vaccine-naïve adults administered a JE-VC two-dose primary series. Methods: We obtained archived sera from U.S. military personnel and performed a 50% plaque reduction neutralization test for anti-JE virus neutralizing antibodies. We compared the geometric mean titer (GMT) and seroprotection rate at 12–23 months after one JE-VC dose in previously JE-MB-vaccinated personnel and after the second JE-VC dose in previously JE vaccine-naïve personnel. Non-inferiority was concluded if the lower bound of the two-sided 95% confidence interval (CI) of the GMT ratio in previously vaccinated to vaccine-naïve personnel was >1/1.5. Results: The GMT in previously JE-MB-vaccinated persons was 75 (95% CI 63–90) and in previously JE vaccine-naïve persons was 12 (95% CI 11–14), and seroprotection rates were 94% (235/250) and 54% (135/250), respectively. The ratio of GMTs was 6.3 (95% CI: 5.0–7.7), satisfying the criterion for non-inferiority. Conclusions: One JE-VC dose in previously JE-MB-vaccinated military personnel provides good protection for at least 1–2 years. The benefits of administration of a single JE-VC dose in previously JE-MB-vaccinated adults include a shorter time to completion of re-vaccination before travel, a decrease in the risk of adverse events, and reduced costs.